2006
DOI: 10.1007/s10350-006-0706-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti- Saccharomyces cerevisiae Antibody in Intestinal Behçet's Disease Patients: Relation to Clinical Course

Abstract: Anti-Saccharomyces cerevisiae antibody positive rate was 44.3 percent in intestinal Behçet's disease. Clinical findings at diagnosis and cumulative relapse rates of intestinal Behçet's disease were not found to be associated with anti-Saccharomyces cerevisiae antibody expression. However, patients with anti-Saccharomyces cerevisiae antibody (+) intestinal Behçet's disease were more likely to receive surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 41 publications
(43 reference statements)
1
26
0
Order By: Relevance
“…Hence, further prospective studies with international validation are needed, and histopathologic and laboratory tests specifi c for intestinal BD, such as HLA-B51 or ASCA (anti-Saccharomyces cerevisiae antibody), might be included in the next version of the criteria. In an anecdotal report, ASCA was reported to be associated with intestinal BD and patients with ASCA were more likely to receive surgical treatment (30) . Finally, because only patients with ulcerations…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Hence, further prospective studies with international validation are needed, and histopathologic and laboratory tests specifi c for intestinal BD, such as HLA-B51 or ASCA (anti-Saccharomyces cerevisiae antibody), might be included in the next version of the criteria. In an anecdotal report, ASCA was reported to be associated with intestinal BD and patients with ASCA were more likely to receive surgical treatment (30) . Finally, because only patients with ulcerations…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Among them the most described were anti-Saccharomyces cerevisiae antibodies (ASCAs) [198][199][200][201] and anti-endothelial cell antibodies (AECAs) [202][203][204][205]. ASCAs were linked more to gastrointestinal manifestations in BD [198][199][200][201][202] and their healthy relatives [201].…”
Section: Autoantibodiesmentioning
confidence: 99%
“…Among them the most described were anti-Saccharomyces cerevisiae antibodies (ASCAs) [198][199][200][201] and anti-endothelial cell antibodies (AECAs) [202][203][204][205]. ASCAs were linked more to gastrointestinal manifestations in BD [198][199][200][201][202] and their healthy relatives [201]. AECA has been implicated with vascular [202,204] and intestinal [205] involvement in BD and several studies demonstrated that alpha-enolase is the target antigen of AECA in BD patients [203][204][205].…”
Section: Autoantibodiesmentioning
confidence: 99%
“…Fresko et al reassessed the level of IgG and IgA ASCA in 85 BD patients and found no significant difference between BD and group of diseased and healthy controls; however, there was a significant trend for patients with gastrointestinal (GI) involvement with BD to be more positive for ASCA compared with the rest of the patients with BD [141]. In another study, ASCA positive rate in BD, intestinal BD and healthy control subjects was shown to be 3.3%, 44.3%, and 8.8% respectively; however, clinical findings at diagnosis and cumulative relapse rates of intestinal BD were not found to be associated with ASCA expression [142]. There is also a report of a relatively high percentage of seropositivity for anti-S. cerevisiae Mannan antibody in patients with Crohn's disease and patients with BD compared with normal controls [143].…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%